Social prescribing in practice: community-centred approaches. (2nd July 2019) - Howarth, Michelle; Burns, Liz
Abstract : More people are living longer with multimorbidities, many of which are handled in general practice.Michelle Howarth andLiz Burns highlight the contribution that general practice nurses can make to providing person-centred approaches to improving health and wellbeing The NHS Long Term Plan recognised the need to understand that 'what matters to someone' is not the same as 'what's the matter with someone'. Conversations that focus on what is the matter with someone typically draw out the patient's needs, with assessment and care planning based on classic principles of pathogenesis and accompanying clinical solutions. Conversations that consider what matters to someone draw out a person's individual assets and what is important to them, with personalised care and support planning based on principles of salutogenesis and non-medical solutions, such as social prescribing. This article explores the pivotal role that practice nurses have in maximising their impact on personalised care and population health for all, including for people living with long-term physical and mental health conditions. It highlights the unique contribution that practice nurses can make in strengthening community-centred approaches to health and wellbeing in primary care.